Education in the context of artificial intelligence: Editorial (Studia Doctoralia Psychology and Educational Science, 2024)
AI or artificial intelligence refers to the field of computer science that focuses on the development of intelligent machines capable of performing tasks that usually require human intelligence (Tahiru, 2021). While it is widely acknowledged that AI technologies cannot address all challenges, there is a perspective suggesting that they can contribute to resolving some of the most critical issues confronting humanity today.